Retinoic Acid Induces Functionally Suppressive Foxp3+RORγt+ T Cells In Vitro - Martínez-Blanco, Mónica; Lozano-Ojalvo, Daniel; Pérez-Rodríguez, Leticia; Benedé, Sara; Molina, Elena; López-Fandiño, Rosina (Frontiers in Immunology, 2021)
Introduction CD4+ T cells with regulatory function co-expressing Foxp3 and RORγt are linked to the development of oral tolerance towards innocuous food antigens in mice. This study aimed to discern the role played by IL-6 and retinoic acid (RA) in the in vitro generation of Foxp3+RORγt+ T cells and to investigate whether such cells have suppressive properties. Methods CD4+CD25- T cells isolated from the spleen of BALB/c mice, were stimulated in the presence of IL-2 alone or together with TFG-β and different concentrations of IL-6 and/or RA. Percentage of Foxp3+, RORγt+, IL-17+, Foxp3+RORγt-, Foxp3+RORγt+, and Foxp3-RORγt+ T cells within the total CD4+ T cell population, production of cytokines (IL-10 and IL-17A) and gene expression (Foxp3, Rorc, Tgfb1, Il6, Il10, and Il17) were assessed at different time points. The phenotype and ability of cells generated from CD4+CD44-CD62L+ cells in the presence of RA to suppress effector T cell proliferation was assessed. Results TGF-β plus IL-6 induced the generation of Foxp3+ and double positive Foxp3+RORγt+ T cells to a higher extent than TGF-β alone at the beginning of the incubation period, although expression of Foxp3 subsequently declined. RA, added to TGF-β, increased Foxp3 and Rorc expression and Foxp3 and RORγt transcription and promoted the differentiation of Foxp3+RORγt- and Foxp3+RORγt+ cells that expressed and secreted IL-17. Foxp3+ T cells generated in vitro in presence of RA were functionally suppressive. Conclusions Under the influence of IL-2 and TGF-β, suppressive Foxp3+RORγt+ T cells that express and secrete IL-17 can be produced in vitro and RA further contributes to stabilize this phenotype.